ANALISIS KUALITAS PELAYANAN ANGGOTA BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) KESEHATAN TINGKAT PERTAMA DITINJAU DARI PELAYANAN PRIMA - Silvia Tuti; Roro Merry Chornelia W (JISIP : Jurnal Ilmu Sosial dan Ilmu Politik, 2019)
Abstract : Public service is closely related to excellent service. Service is said to be excellent if public service can fulfill the best service from government to customer/service user. This study aimed to determine the quality of services and the supporting and inhibiting factors and the impact of Quality Service of BPJS Kesehatan at Puskesmas Beji. This study is a qualitative research type. The data collection techniques used observation, interviews, and documentation. The results obtained were (1) the service quality in term of an excellent service was prerequisite of service, Clarity of Service Officer, discipline of service officer, ability of service officer, justice to get service, Courtesy and Friendliness Officer, Fairness of Service Cost, Certainty of Service and service schedule, comfortable Environment and Service Procedures, Service Officer responsibilities, Service Speed and Service Security need to be improved. (2) Supporting factors of service, the discipline of service officers, justice to get services, fairness of service cost, comfortable environment and service inhibiting factors, service procedures, lack of responsibilities of service personnel, slow service, and service security was still low. (3) The impact of the quality of service was the fulfillment of the basic needs of the patient's health either by promotive, preventive, curative and rehabilitative. Keywords: Service Quality, Excellent Service. Abstrak: Pelayanan publik erat kaitannya dengan pelayanan prima. Pelayanan dikatakan prima apabila pelayanan publik dapat memenuhi pelayanan yang terbaik dari pemerintah kepada pelanggan/pengguna jasa. Penelitian ini bertujuan untuk mengetahui kualitas pelayanan dan faktor pendukung dan penghambat serta dampak Kualitas Pelayanan Anggota BPJS Kesehatan pada Puskesmas Beji. Penelitian ini menggunakan jenis penelitian ini kualitatif. Hasil yang diperoleh adalah (1) Kualitas Pelayanan dengan menggunakan sendi pelayanan prima yaitu prasyarat pelayanan, Kejelasan Petugas Pelayanan, kedisplinanan petugas pelayanan, kemampuan petugas pelayanan, keadilan mendapatkan pelayanan, Kesopanan dan Keramahan Petugas, Kewajaran Biaya Pelayanan, Kepastian Biaya Pelayanan, Kepastian Jadwal Pelayanan, Kenyamanan Lingkungan serta Prosedur Pelayanan, Tanggungjawab Petugas Pelayanan, Kecepatan Pelayanan dan Keamanan Pelayanan perlu diperbaiki. (2) Faktor pendukung pelayanan, Kedisplinan petugas pelayanan, keadilan mendapatkan pelayanan, kewajaran biaya pelayanan, kenyamanan lingkungan dan faktor penghambat pelayanan, prosedur pelayanan, kurangnya tanggungjawab petugas pelayanan, kecepatan pelayanan masih kurang,  dan keamanan pelayanan masih rendah. (3) Dampak dari kualitas pelayanan adalah terpenuhinya kebutuhan dasar kesehatan pasien baik secara promotif, preventif, kuratif maupun rehabilitatif. Kata Kunci: Kualitas Pelayanan, Pelayanan Prima